Organic functional group preparations. - Sandler, Stanley R., 1935- (Organic chemistry (New York, N.Y.) ;, 1989)
This volume provides organic chemists with a convenient, up-to-date reference source on reliable preparative procedures for the most common functional groups. Preparations for each functional group have been subdivided into various reaction types.